Institutional environment and access to microfinance by self-employed women in the rural areas of Edo state - Okojie, Christiana; Monye-Emina, A.; Eghafona, K.; Osaghae, G.; Ehiakhamen, J. O. (International Food Policy Research Institute, 2010)
In Nigeria, conventional financial institutions serve only about 35 percent of the active population, and the poor, especially women, have limited access to financial services. Private sector-led microfinance institutions (MFIs) are increasingly playing a role to fill this need. This brief provides an overview of the institutional environment of microfinance in Nigeria, as well as insights and recommendations for better reaching this audience, based on focus group discussions and case studies of self-employed women in rural areas of Edo State, Nigeria.